The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/rrq.343
|View full text |Cite
|
Sign up to set email alerts
|

How the Reading for Understanding Initiative’s Research Complicates the Simple View of Reading Invoked in the Science of Reading

Abstract: Advocates of the science of reading have invoked the simple view of reading (SVR) to justify an approach that foregrounds decoding in early reading instruction. The SVR, which describes comprehension as the product of decoding and listening comprehension, also served as the primary theoretical model underlying the Reading for Understanding (RfU) initiative. Research funded under the RfU initiative included direct examinations of the validity of the SVR and the nature of its underlying components and extended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 68 publications
1
42
0
5
Order By: Relevance
“…A substantial body of emerging scientific findings, including our own, suggests that the SVR' s elegant simplicity may mask contributions to reading comprehension that could-and should-inform research, practice, and ultimately, the science of reading (for reviews, see Cervetti et al, 2020;Snowling & Hulme, 2012). In particular, the original independent, two-factor SVR model, and its typical implementation in practice, disallows commonalities between D and LC and, occasionally, neglects scientific findings that LC contributes directly to D-and to reading comprehension through D-partially explaining the substantial shared variance between these constructs (e.g., Cartwright, Lee, et al, 2020;Tunmer & Chapman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of emerging scientific findings, including our own, suggests that the SVR' s elegant simplicity may mask contributions to reading comprehension that could-and should-inform research, practice, and ultimately, the science of reading (for reviews, see Cervetti et al, 2020;Snowling & Hulme, 2012). In particular, the original independent, two-factor SVR model, and its typical implementation in practice, disallows commonalities between D and LC and, occasionally, neglects scientific findings that LC contributes directly to D-and to reading comprehension through D-partially explaining the substantial shared variance between these constructs (e.g., Cartwright, Lee, et al, 2020;Tunmer & Chapman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When readers have well-developed vocabulary and language proficiency, higher-level skills appear to be the main source of variability in reading comprehension in differentiating groups. Foundational oral language skills such as vocabulary and grammatical knowledge underlie higher-level skills such as making inferences and comprehension monitoring, which in turn, are necessary for reading comprehension success (Cervetti et al, 2020;Kim, 2017). Comprehension of conjunctions can enhance reading comprehension and has also been found to predict reading comprehension in ELLs ( (Crosson & Lesaux, 2013;Crosson, Lesaux, & Martiniello, 2008); Droop & Verhoeven, 2003;(Geva, 2007;Geva & Ryan, 1993;Welie, Schoonen, Kuiken, & van den Bergh, 2017)).…”
Section: Higher-level Skillsmentioning
confidence: 99%
“…This gen eral model gives equal weight to decoding and compre hension and predicts that children with deficits in either domain will have reading problems. There is a wide body of research that has supported and expanded the simple view of reading (Cervetti et al, 2020), emphasizing the need for both decoding and linguistic comprehension skills and questioning whether the two strands are distinct in the early years (Dickinson, Nesbitt, & Hofer, 2019). Significantly, this newer research has shown that pre school oral language development predicts reading com prehension at grade 3 (Language and Reading Research Consortium & Chiu, 2018) and that reading comprehen sion and decoding do not emerge as distinctly measurable constructs until grade 3 (Lonigan & Burgess, 2017).…”
Section: History and Models Of Early Reading Developmentmentioning
confidence: 99%